Source data for Kinetic and structural mechanism for DNA unwinding by a non-hexameric helicase - Carney, Sean; Ma, Wen; Chemla , Yann (University of Illinois at Urbana-Champaign, 2021)
This dataset includes the source data for Figures 1-4 and supplementary figures 1-10 for the manuscript "Kinetic and structural mechanism for DNA unwinding by a non-hexameric helicase".